Aminoglycosides for infective endocarditis: time to say goodbye?. (June 2020) - Lebeaux, D.; Fernández-Hidalgo, N.; Pilmis, B.; Tattevin, P.; Mainardi, J.-L.
Abstract: Background: Based on experimental studies showing synergism with β-lactams and glycopeptides, aminoglycosides have long been considered essential in the treatment of infective endocarditis (IE). However, their use is associated with a high risk of renal failure, especially in elderly patients. Aims: The aim of this narrative review was to summarize the evidence to support reducing or even avoiding the use of aminoglycosides for the treatment of IE. We also analysed data supporting the use of aminoglycosides in specific subgroup of IE patients. Sources: PubMed database was searched up to July 2019 to identify relevant studies. Contents: Recent European Guidelines reduced the use of aminoglycosides in IE, no longer recommended in Staphylococcus aureus native-valve IE, and shortened to 2 weeks for IE related to Enterococcus faecalis and streptococci with penicillin MIC >0.125 μg/mL. In addition, an alternative regimen without aminoglycosides (ampicillin or amoxicillin plus ceftriaxone) is proposed for E. faecalis . Observational studies suggested that gentamicin would not be necessary in the case of staphylococcal prosthetic valve IE as long as rifampicin is maintained. Recent clinical studies showed that for streptococcal IE, gentamicin could be restricted to isolates with penicillin MIC >0.5 μg/mL. For the empirical and definitive treatment of E. faecalis IE, amoxicillin or ampicillin plus ceftriaxone may be considered, irrespective of high-level of aminoglycoside resistance. Implications: In a scenario of progressive increase in the age and frailty of IE patients, the use of aminoglycosides can be reduced or avoided in 90% cases. This should result in reduced incidence of renal failure, an important prognostic factor in IE.